Removal of cadmium from water using biosorption process - Dai, Xiao Jia (2021)
Human activities such as mining, industrialization and agricultural activities largely contribute to the release of divalent heavy metals such as cadmium had led to contamination of water sources. Cadmium contamination in water will directly threaten the human health. Therefore, the established threshold concentration of cadmium in raw water by World Health Organization (WHO) is 0.003 mg/L only. The technical feasibility of biosorption process which utilizing low-cost biosorbents in removing cadmium from water was evaluated in this project. Overall, the literature review in this project was conducted by narrative review approach. The relevant information on the biosorbents that had been used in the removal of cadmium from water was obtained through different online sources and the literatures were screened according to the pre-set criteria: 1) literatures published on past 12 years, 2) important keywords are included, 3) published in English language, 4) proper citation and references. After that, the relevant experimental data were extracted from the literatures and gathered using Excel database and dialogical narrative analysis was implemented in presenting the findings for this research work. Among different types of biosorbents, agricultural wastes were found to be the most efficient biosorbent for cadmium removal. From the effect of parameters study, it was discovered that the maximum cadmium uptake was normally obtained at slightly acidic to neutral solution pH, high solution to biosorbent dosage ratio and optimum contact time of within three hours. The responsible functional groups in cadmium biosorption are acidic, amino, hydroxyl and carboxyl groups. The biosorption of cadmium are reported to follow Langmuir isotherms and pseudosecond order kinetic models. From the results analysis, it is predicted that avocado peel has potential to be a promising biosorbent in removing cadmium from water where the biosorption process is predicted to happen at a condition of pH = 4−7, solution to biosorbent dosage ratio ≤1000 mL/g and contact time within three hours. In conclusion, biosorption process is efficient in removing cadmium from water as it is environmentally friendly and cost effective.